Pelatihan Pembuatan Alat Penabur Pupuk Jagung Sederhana untuk Gabungan Kelompok Tani Desa Mojokrapak - Waslah Waslah; Asiatun Yani; Latifatul Bariroh (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The training on making a simple corn fertilizer sowing tool is the Association of Farmers Group (GAPOKTAN) in Mojokrapak village, Tembelang district. Based on the situation analysis, problems emerged, including: Many farmers are elderly and prone to illness, there are still many farmers who fertilize corn manually without using tools and there is a need for tool innovation to help farmers make their work more effective in agriculture. farmers' knowledge and understanding of new innovations, utilizing simple tools without the need for large costs to assist the process of fertilizing corn plants. The methods used are socialization, training, and face-to-face assistance and the results Growing knowledge and insight into the target group, namely Gapoktan in Mojokrapak Village, especially elderly farmers and growing knowledge and insight about new innovation tools by using simple materials at affordable costs